Analisis Taksonomi Pengaruh Promosi Kesehatan Terhadap Pengetahuan Pemandu Wisata Terkait Risiko Kesehatan Wisata - Harpiana Rahman; Rezky Aulia Yusuf; Zulkhair Burhan; Haryudi Rahman (Window of Public Health Journal, 2026)
River tubing tourist attractions are a developing destination with tourism potential. However, this service is separate from a health risk prevention promotion service. Initial studies show that the absence of health information services in tourism services causes limitations in tour guides in developing appropriate health information needed by tourists. This study aimed to analyze changes in tour guide knowledge related to the importance of implementing health risk prevention and accident risks in tourist attractions. The type of research used is quantitative research with a case study approach. Informants were selected based on the criteria of being river tubing tour guides, several tour guide officers in river tubing, namely 5 informants. The results of the taxonomic analysis showed an increase in tour guide knowledge related to the prevention of health risks and accident risks that tourism activities can cause. These findings have practical implications, as they suggest that tour guides, in carrying out their duties, can also provide health education to tourists to prevent health risks and accidents, thereby enhancing the overall tourism experience.